ANALYSIS OF GREEN ACCOUNTING IMPLEMENTATION AT PT TIMAH (COMPANY) Tbk - Dwi Jaladri, Narendra; Mulyani, Sri (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2020)
Timah is a mining company in the province of Bangka Belitung and is a pride of its people, although the presence of tin mining can be directly dangerous to the environment such as forests and water pollution. However, PT Timah has carried out environmental conservation and empowerment activities for the local community. The purpose of this study is to analyze the implementation of environmental accounting related to financial reporting. As a large mining company, it is fitting for PT Timah to pay attention to the environment and living conditions of the surrounding community as a result of its mining activities. By using descriptive methods, and quantitative approaches and data collection from reliable sources concluded that PT Timah has a good action on the environment. The results of this study will improve the good image of PT Timah. PT Timah has taken sufficiently good steps to preserve the environment after the mining. Every year, the Company always plans to reclaim land of up to 2,000 ha.